Influence of Garlic on the Glycemic Control and Lipid Profile in Animals with Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-analysis - Shojaei-Zarghani, Sara; Najafi, Nastaran; Fattahi, Mohammad Reza; Safarpour, Ali Reza (Planta Medica, 2023)
Nonalcoholic fatty liver disease is the hepatic sign of metabolic syndrome. Here, we aimed to assess the effects of garlic and its major components on fasting plasma glucose, fasting insulin, and lipid profile levels in animal models of nonalcoholic fatty liver disease. A systematic search in PubMed, Scopus, ProQuest, and Web of Science was performed. After the screening process and data extraction, the pooled effect sizes were estimated using a random-effect model and stated as standardized mean differences and a 95% confidence interval. Out of 839 reports, 22 articles were included in the present study. The pooled results revealed that garlic and its components significantly decreased fasting plasma glucose (standardized mean difference: − 0.77, 95% confidence interval: − 1.42 to − 0.12, I2: 58.85%), fasting insulin (standardized mean difference: − 1.88, 95% confidence interval: − 3.07 to − 0.69, I2: 70.42%), serum triglyceride (standardized mean difference: − 1.01, 95% confidence interval: − 1.43 to − 0.59, I2: 61.41%), cholesterol (standardized mean difference: − 1.00, 95% confidence interval: − 1.39 to − 0.60, I2: 52.12%), and low-density lipoprotein cholesterol (standardized mean difference: − 0.98, 95% CI: − 1.63 to − 0.32, I2: 71.58%) and increased high-density lipoprotein cholesterol (standardized mean difference: 1.05, 95% confidence interval: 0.52 to 1.58, I2: 59.39%) levels. The type of animal, nonalcoholic fatty liver disease induction model, kind and duration of intervention, study model, and risk of bias were detected as possible sources of heterogeneity across studies. We conclude that garlic and its major components have a favorable impact on glycemic control and lipid profile in diet-induced nonalcoholic fatty liver disease animal models.
Keywords: Garlic; Allium sativum; Amaryllidaceae; insulin resistance; lipid profile; nonalcoholic fatty liver disease